Don't forget about customer magazines: the effects of reading experiences on customer magazine effectiveness - Koob, Clemens (Frontiers in Communication, 2023)
Introduction: Content marketing continues to gain importance in organizations’ marketing mix. However, its effectiveness has received little academic attention. This is particularly true of customer magazines, which, despite increasing digitization, remain a key pillar of content marketing and account for considerable investments. Therefore, this paper examines how reading experiences affect the effectiveness of customer magazines, mediated by media engagement. Methods: Based on the uses-and-gratifications-theory and literature on sensory perception, journalistic quality, and media engagement, several hypotheses are proposed. To investigate the hypotheses, the study uses a cross-sectional survey. The dataset for the analyses consists of 1396 consumers and is analyzed by structural equation modeling. Results: The results indicate that hedonically gratifying, as well as identity-enforcing content experiences and visually and haptically gratifying process experiences are associated with higher effectiveness. Media engagement mediates these effects. Experienced journalistic quality directly and positively influences customer magazine effectiveness. Discussion: This study’s findings are important to marketing communications research. In particular, the study contributes to the still limited literature on content marketing effectiveness and helps practitioners optimize customer magazines.